ANALISIS EFISIENSI LEASING DALAM MANAJEMEN ASET PERUSAHAAN - Nazwa Fatimah Az-Zahra; Mutiara Aura Ramadhan; Aditya Raffi Noval Pratama; Mochammad Rafli Putra Iqbal (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
The history of the development of the leasing business in Indonesia began to emerge since 1974, the legal regulation of problematic financing in leasing agreements is in the Joint Decree of the Minister of Finance, Minister of Industry and Minister of Trade. Leasing is classified as an unnamed agreement (innominaat contracten), because it is not regulated in the Civil Code and has not been specifically regulated in the Law, but is an agreement that arises, grows, and develops in society. This analysis uses the library research method (literature study), which is research conducted by reading books or magazines with other data sources in the library. And by using analytical techniques that involve identifying main themes, creating categories, and interpreting data. The efficiency of leasing in corporate asset management can be compared with other methods such as direct purchase, borrowing, and leasing. In terms of cost, leasing reduces upfront capital expenditure, while outright purchase requires a large investment. Leasing also offers higher flexibility, allowing companies to renew assets periodically without the risk of depreciation, in contrast to outright purchase which is tied to the residual value of the asset. When compared to loans, leasing has a fixed payment structure and often includes maintenance, while loans require principal and interest payments, and increase the debt burden.